Young Zeus - Karas, G. Brian (New York : Scholastic Press, 2010)
With the help of six monsters, five gods, an enchanted she-goat, and his mother, young Zeus becomes the god of gods, master of lightning and thunder, and ruler over all.
Publisher's Weekly
School Library Journal starred
Publisher's Weekly, January 2010
School Library Journal starred, February 2010
3.0
K-3
Keywords: Zeus (Greek deity) -- Childhood -- Juvenile literature; Zeus (Greek deity); Zeus (Greek deity); Picture books for children